2016
DOI: 10.3390/su8121272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Sustainability of Nature Reserves Using an Ecological Footprint Method: A Case Study in China

Abstract: Nature reserves are established to protect ecosystems and rare flora and fauna. However, with the rapid development of the social economy, many nature reserves are facing enormous pressures from human activities. The assessment of the sustainability of nature reserves is a fundamental task for the planning and management of such areas. In this study, the sustainability of China's 319 national nature reserves (NRRs) was evaluated based on an ecological footprint (EF) method. The results indicated that the per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Additionally, legislation should be implemented to protect wetland and forestland that serve the key leading role of storing large amounts of biomass carbon over time. In 1998, the Chinese government completed the 'The Land Administration Law of the People's Republic of China' and formulated a systematic land protection policy at a national scale (Wang et al, 2003;Liu et al, 2016). At the provincial level, Huangnong River Provincial Nature Reserve of Jilin Province was formally established in 2000, and Jilin Hunchun Northeast Tiger Nature Reserve was formally established in 2001.…”
Section: Implications and Future Perspectivesmentioning
confidence: 99%
“…Additionally, legislation should be implemented to protect wetland and forestland that serve the key leading role of storing large amounts of biomass carbon over time. In 1998, the Chinese government completed the 'The Land Administration Law of the People's Republic of China' and formulated a systematic land protection policy at a national scale (Wang et al, 2003;Liu et al, 2016). At the provincial level, Huangnong River Provincial Nature Reserve of Jilin Province was formally established in 2000, and Jilin Hunchun Northeast Tiger Nature Reserve was formally established in 2001.…”
Section: Implications and Future Perspectivesmentioning
confidence: 99%
“…Zhen and Du [23] suggested that the Grain for Green program increased the biological capacity (BC) of forest and grassland, but it also decreased the BC of cultivated land. In addition, some literatures has investigated the new agricultural animal husbandry projects (such as the "hog-biogas-fish" system) [37], national nature reserves [38], the ecological footprint of food consumption of residents [39,40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In China, Gu [5] analyzed the ecological footprint of urban agglomeration in the middle reaches of the Yangtze River and found that the local ecological deficit was serious. Liu et al [6] evaluated 319 natural reserves in China with ecological footprint analysis, which provides a powerful reference for decisions on protection of natural reserves. Chen [7] studied the sustainability of ecological environment in Xinjing district, Taiwan with emergetic ecological footprint model and ecological safety assessment to ensure the balance between ecological protection and tourism development.…”
Section: Introductionmentioning
confidence: 99%